Next generation sequencing and functional analysis of patient urine renal progenitor-derived podocytes to unravel the diagnosis underlying refractory lupus nephritis - Romagnani, Paola; Giglio, Sabrina; Angelotti, Maria Lucia; Provenzano, Aldesia; Becherucci, Francesca; Mazzinghi, Benedetta; Mueller, Susanna; Amann, Kerstin Ute; Weidenbusch, Marc; Romoli, Simone; Lazzeri, Elena; Anders, Hans-Joachim (Nephrology Dialysis Transplantation, 2016)
Often the cause of refractory lupus nephritis (RLN) remains unclear. We performed next-generation sequencing for podocyte genes in an RLN patient and identified compound heterozygosity for APOL1 risk alleles G1 and G2 and a novel homozygous c.[1049C>T]+[1049C>T] NPHS1 gene variant of unknown significance. To test for causality renal progenitor cells isolated from urine of this patient were differentiated into podocytes in vitro. Podocytes revealed aberrant nephrin trafficking, cytoskeletal structure and lysosomal leakage, and increased detachment as compared with podocytes isolated from controls. Thus, lupus podocytopathy can be confirmed as a cause of RLN by functional genetics on patient-derived podocytes.
EVALuna2:25516